Paradigms, Limitations, Opportunities, and Challenges of E-Sports in Indonesia - Nico Fadila Rahman; Anton Komaini; Asep Sujana Wahyuri; Eri Barlian; Rahmi Muthia; Fiky Zarya (Jurnal Pendidikan dan Pengajaran, 2023)
The development of increasingly advanced technology certainly also affects developments in the world of sports. The emergence of sports technology or better known as Esports is one of the most pronounced influences of technological developments in the world of sports today. In Indonesia, Esports has been recognized as one of the sports by inaugurating PBESI (Indonesian Esports Executive Board) in 2020. Even though a new sport has been inaugurated, there are still many problems related to this Esports. The problems faced include: there are still many questions about why Esports is included in sports, people's views on Esports, understanding what Esports is and how it differs from games, and about the impact of Esports. This study aims to get a deeper picture and information about this Esports sport, especially about the paradigms, limits, opportunities and challenges of Esports in Indonesia. This type of research is a qualitative study with an exploratory descriptive approach. This study used purposive sampling techniques. The participants involved were 12 people consisting of 3 West Sumatra ESI administrators, 2 Esports athletes, 1 sports lecturer, 2 game players, and 4 related community members (business people, parents, teachers and lecturers, health workers). The results of this study show that Esports is a technological sport. The lack of understanding about Esports makes a difference in views on Esports. Esports and games have certain restrictions, where Esports is indeed a game but not all games are included in Esports.